Anorexia nervosa in a child with cerebral palsy - Yukia Nishiue; Dai Miyawaki; Moe Koki; Tomoko Harada (PCN Reports, 2025)
Abstract Background There have been no reports of children with cerebral palsy (CP) developing anorexia nervosa (AN). This report presents a 13‐year‐old girl with CP who was hospitalized in a state of severe underweight and impaired consciousness, and was subsequently diagnosed and treated for AN. Case Presentation The patient is a 13‐year‐old girl diagnosed with CP, who relied on a wheelchair for mobility. Her weight consistently remained at −2 standard deviations. She began restricting her food intake after comparing her body to her sister's and receiving comments from caregivers about her weight. Consequently, her body mass index dropped to 8.2, and when admitted, she showed impaired consciousness. After intensive care treatment, she was hospitalized in the psychiatric ward for about 6 months before discharge. Despite extensive rehabilitation, her physical abilities at discharge did not return to preillness levels. Conclusion This case indicates that diagnosing and assessing AN in children with CP can be particularly challenging. Children with CP who develop AN are prone to rapid progression to severe physical conditions; therefore, early consultation with a specialist is strongly recommended.